Utilization of—Omic technologies in cold climate hydrocarbon bioremediation: a text-mining approach - Abdullah, Kristopher; Wilkins, Daniel; Ferrari, Belinda C. (Frontiers in Microbiology, 2023)
Hydrocarbon spills in cold climates are a prominent and enduring form of anthropogenic contamination. Bioremediation is one of a suite of remediation tools, that has emerged as a cost-effective strategy for transforming these contaminants in soil, ideally into less harmful products. However, little is understood about the molecular mechanisms driving these complex, microbially mediated processes. The emergence of -omic technologies has led to a revolution within the sphere of environmental microbiology allowing for the identification and study of so called ‘unculturable’ organisms. In the last decade, -omic technologies have emerged as a powerful tool in filling this gap in our knowledge on the interactions between these organisms and their environment in vivo. Here, we utilise the text mining software Vosviewer to process meta-data and visualise key trends relating to cold climate bioremediation projects. The results of text mining of the literature revealed a shift over time from optimizing bioremediation experiments on the macro/community level to, in more recent years focusing on individual organisms of interest, interactions within the microbiome and the investigation of novel metabolic degradation pathways. This shift in research focus was made possible in large part by the rise of omics studies allowing research to focus not only what organisms/metabolic pathways are present but those which are functional. However, all is not harmonious, as the development of downstream analytical methods and associated processing tools have outpaced sample preparation methods, especially when dealing with the unique challenges posed when analysing soil-based samples.